Influences of soldering time on wettability and intermetallic phase between Sn-3.0Cu solder and copper substrate - Mookam, Niwat; Kanlayasiri, Kannachai (My University, 2018)
In this paper, the influences of soldering time on the wettability and intermetallic phase between Sn-3.0Cu lead-free solder and copper substrate were investigated. Reflow soldering was performed at 350 ° C under variable soldering times of 10, 20, 40, 60, 120, 240 and 480 s. The results indicated that the wettability and intermetallic growth depend on the soldering time. In addition, the Cu6Sn5 and Cu3Sn intermetallic phases with a hexagonal crystal structure were found between the lead-free solder and the copper substrate. The growth of intermetallic phases increased with soldering time, and the growth of intermetallic phases remarkably depended on grain boundary diffusion and was volume diffusion-controlled for Cu6Sn5 and Cu3Sn, respectively.